Effects of supplementing a polyphenol-rich sugarcane extract through drinking water on egg production and quality of laying hens - Namalika D. Karunaratne; Sasmitha De Silva; Minoli Herath; Ruvini Liyanage; Pabodha Weththasinghe; Barana C. Jayawardana; Eranga De Seram; Anil Pushpakumara; Mathew Flavel (PLoS ONE, 2025)
Polyphenols are a wide group of naturally occurring compounds found in plants and have the potential to safeguard living cells. The objective was to evaluate whether the inclusion of a polyphenol-rich sugarcane extract (PRSE) in drinking water could improve egg production and the quality of commercial layers. A total of 120 Shaver Brown hens, aged 43 weeks, were randomly allocated to 12 litter-floor pens in two open-sided poultry houses. The pens were divided into two treatment groups: one receiving 0% (control) and the other 0.05% PRSE in drinking water throughout the study duration. The treatments were prepared by adding PRSE manually into the drinking water daily, and water was given ad libitum. The birds were given commercial layer feed throughout the study. The number of eggs produced, abnormal eggs, and mortality were recorded daily. Egg weight, yolk colour, yolk height, albumen height, Haugh units, and antioxidant properties, were measured at weeks 45, 47 and 49. Supplementing PRSE in the drinking water did not impact hen-day egg production, hen-housed egg production, egg weight, egg mass, or feed conversion ratio. However, there was a trend toward significance in egg weight at week 45. The results indicated that PRSE supplementation led to a significant reduction in yolk colour during week 45 (P = 0.001), although no differences were observed in subsequent weeks. Yolk height, thick albumen height, and haugh units were unaffected by the treatment, while thin albumen height showed a trend towards reduction in the PRSE group at weeks 47 and 49 (P = 0.05). The DPPH assay revealed a significant increase in antioxidant capacity in the PRSE group at week 45 (P = 0.02). The 0.05% PRSE supplementation in drinking water initially enhanced antioxidant capacity but later adversely affected yolk color and thin albumen height.